The free bilamellar autograft (FBA) procedure: A comprehensive case series of an alternative surgical approach to reconstruction of large eyelid defects - McDonald, Heather M.; McDonald, Katherine A.; McDonald, Hector (Frontiers in Surgery, 2023)
Purpose The free bilamellar autograft (FBA) procedure involves harvesting a free, full-thickness section of eyelid tissue from one of the patient’s healthy eyelids to reconstruct a large defect of the involved eyelid. No vascular augmentation is employed. The purpose of this study was to determine the structural and cosmetic results of this procedure. Methods A case series was performed, looking at patients who underwent the FBA procedure for large, full-thickness eyelid defects (>50% eyelid length) between 2009 and 2020 at a single oculoplastic surgical centre. Basal cell carcinomas most frequently met criteria for the procedure. OHSN-REB waived ethics approval. All surgeries were performed by one surgeon. A single operation, with surgical steps reported in detail, was completed with follow-up documentation at ideally 1 day, 1 week, 1 month, 3 months, 6 months, and 1 year. The mean follow-up period was 28 months. Results Thirty-one patients (17 males, 14 females, mean age 78-years-old) were included in the case series. Comorbidities included diabetes and smoking. Most patients had known basal cell carcinomas removed from the upper or lower eyelid. The mean widths of the recipient and donor sites were 18.8 and 11.5 mm, respectively. All 31 FBA surgeries resulted in structurally functional, cosmetically pleasing, and viable eyelids. Six patients developed minor graft dehiscence, 3 developed an ectropion, and 1 developed mild superficial graft necrosis secondary to frostbite, which fully recovered. Three healing phases were identified. Conclusion This case series adds to the currently sparse data on the free bilamellar autograft procedure. The surgical technique is clearly articulated and illustrated. The FBA procedure is a simple and efficient alternative to current surgical techniques in the reconstruction of full-thickness upper and lower eyelid defects. The FBA provides functional and cosmetic success, despite the absence of an intact blood supply, with decreased operative time and faster recovery.